A method for preparing indole-modified biomass uranium adsorption material
The indole-modified biomass uranium adsorption material addresses the inefficiencies of current biomass materials by using a simple, cost-effective preparation process to achieve high adsorption capacity and reusability for uranyl ions, ensuring environmental safety.
Patent Information
- Application Number
- CN202410646679.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-23
AI Technical Summary
Current biomass-based adsorption materials for uranium removal have complex preparation processes, high production costs, and low adsorption rates, necessitating a more efficient and cost-effective method using renewable biomass materials.
A method involving the preparation of indole-modified biomass uranium adsorption materials through grafting biomass materials with indole or its derivatives, adding a crosslinking agent, and freeze-drying to create a hydrogel that effectively adsorbs uranyl ions.
The method results in a material with high adsorption performance, low production costs, and environmental safety, achieving an adsorption capacity of up to 900 mg/g and high reusability without causing secondary pollution.
Smart Images

Figure CN118594495B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nuclear wastewater treatment, and specifically relates to a method for preparing an indole-modified biomass uranium adsorption material. Background Art
[0002] As an efficient, clean and environmentally friendly energy source, nuclear energy can effectively make up for the greenhouse gas emissions and environmental pollution problems that occur during the use of traditional energy. Uranium is an important raw material in nuclear fuel and is also the main element with strong radioactivity in nuclear waste. In the water environment, uranium usually exists in a hexavalent form (i.e., uranyl ion). It has strong mobility and can easily enter the human body through the food chain. Excessive accumulation of uranium can damage various organs of the human body and can even lead to death in severe cases. The World Health Organization stipulates that the concentration of uranium in discharged wastewater shall not exceed 30μg L -1 Therefore, the treatment of uranium-containing wastewater has become one of the important issues of public safety, civil safety and environmental protection.
[0003] So far, many methods have been proposed to remove uranium from wastewater, including chemical precipitation, membrane separation, ion exchange, advanced oxidation, photocatalysis and adsorption. Among them, adsorption is widely used in environmental remediation due to its low cost, simple operation and high efficiency. The selection of adsorbent materials is the key to uranium removal by adsorption.
[0004] Biomass materials refer to renewable plant materials and related waste materials that mainly contain cellulose, hemicellulose and lignin. They can be naturally degraded into harmless organic matter in nature and absorbed and utilized by the soil without causing secondary pollution. However, the adsorption materials currently prepared from biomass have complex preparation processes, high production costs, and low adsorption rates for uranium. Therefore, it is particularly important to develop a material that uses biomass materials to perform good adsorption of uranium. Summary of the invention
[0005] The invention aims to provide a method for preparing an indole-modified biomass uranium adsorption material in view of the above technologies. The method uses biomass materials and indole or its derivatives as raw materials, prepares a grafted hydrogel by grafting, further adds a crosslinking agent to the hydrogel, and controls parameters to prepare an indole-modified biomass material that can be used for uranyl ion adsorption; the prepared material has a good adsorption performance for uranyl ions and can be used as a candidate material for green and sustainable development.
[0006] In order to achieve the above invention object, the specific technical solution of the present invention is:
[0007] A method for preparing an indole-modified biomass uranium adsorption material (adsorbent), comprising the following steps: 1) mixing a biomass material with a solvent and adding the mixture to indole or a derivative thereof, adding a catalyst, stirring the mixture, and heating the mixture to a certain temperature to react;
[0008] 2) adding a crosslinking agent to the substance obtained in step 1), and continuing the reaction for a period of time to obtain a wet gel;
[0009] 3) exchanging solvents on the wet gel obtained in step 2) to remove residual reactants;
[0010] 4) freeze-drying the substance obtained in step 3) to obtain an indole-modified biomass uranium adsorption material (adsorbent).
[0011] As a better embodiment of the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorbent material, the biomass material is selected from chitosan or lignin, or a mixture of chitosan, lignin and any one of xanthan gum and guar gum (such as a mixture of chitosan and xanthan gum, or a mixture of chitosan and guar gum, or a mixture of lignin and xanthan gum, or a mixture of lignin and guar gum).
[0012] As a preferred embodiment of the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorption material, the solvent is formamide.
[0013] As a better implementation in the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorption material, the indole or its derivative described in step 1) is selected from 3-indoleacetic acid, 5-hydroxytryptophan, 4-hydroxyindole, 5-hydroxyindole; and the catalyst is p-toluenesulfonic acid monohydrate.
[0014] As a better embodiment of the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorption material, the molar ratio of the biomass material to indole or its derivatives in step 1) is 1:1-1:6.
[0015] As a better implementation in the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorption material, the concentration range of the added amount of the solvent and the material composition is 1-200 mg / L.
[0016] As a preferred embodiment of the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorbent material, the amount of the catalyst p-toluenesulfonic acid monohydrate added is 10wt%-80wt% of the biomass material.
[0017] As a better implementation in the present application, in step 1) of the method for preparing the indole-modified biomass uranium adsorbent material, stirring and heating to 60±10° C. are performed for 24 hours.
[0018] As a better embodiment of the present application, in step 2) of the method for preparing the indole-modified biomass uranium adsorption material, the cross-linking agent is glutaraldehyde, and the amount of the cross-linking agent added is 10wt%-30wt% of the biomass material; the reaction time in step 2) is 12-24 hours.
[0019] As a better embodiment of the present application, in the preparation method of the indole-modified biomass uranium adsorbent material, the wet gel is subjected to solvent exchange in step 3) to remove the residual reactant solvent. The specific steps are: during the exchange, acetone and deionized water are used to exchange the solvent in sequence until the filtrate is neutral, indicating that the p-toluenesulfonic acid monohydrate and the reactant are completely removed.
[0020] As a better embodiment of the present application, in step 4) of the method for preparing the indole-modified biomass uranium adsorbent material, the freeze-drying conditions are as follows: the wet gel is frozen at -10°C for 24-48 hours, then freeze-dried at -50°C and vacuum below 10Pa for 3-5 days, then taken out and naturally heated, and after the sample temperature rises to room temperature, it is taken out and dried in a 45°C oven for 1-2 hours.
[0021] Another object of the present invention is to protect an indole-modified biomass uranium adsorption material prepared according to any one of the above methods or any combination of the methods.
[0022] The third invention object of the present invention is to protect the application of the indole-modified biomass uranium adsorption material mentioned above, which is used for treating uranium-containing wastewater; the maximum adsorption capacity is 900 mg / g.
[0023] The method for determining the uranium adsorption in this application is as follows: add the adsorbent material to 10 mL of U(VI) solution (10-250 mg L -1 ), the pH value range is 2.0-7.5, and stirring is carried out at 298K for 0-360min. The uranium adsorption amount of the adsorbent material is measured, which proves that it has a good adsorption effect.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The preparation method of the present invention is simple and easy to implement, the raw materials are easy to obtain, the cost is low, and the process is simple.
[0026] (ii) The raw materials of the adsorbent prepared by the present invention are all biomass materials, which can be naturally degraded into harmless organic matter in nature and absorbed and utilized by the soil without causing secondary pollution.
[0027] (III) The adsorbent prepared by the present invention has excellent adsorption performance for uranyl ions, high adsorption efficiency and high reusability.
[0028] (iv) The adsorbent prepared by the present invention will not dissolve toxic or harmful substances or ions during use. Therefore, the adsorbent prepared by the method is safer and more effective during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention is a flow chart of the preparation process of the indole-modified biomass uranium adsorption material.
[0030] Figure 2 This is a scanning electron microscope (SEM) image of the microscopic morphology of the adsorbent in Example 1 of the present invention.
[0031] Figure 3 This is a diagram showing the adsorption effect of the adsorbent on uranium at different pH values in Example 1 of the present invention.
[0032] Figure 4 This is a graph showing the variation of the adsorption amount of uranium by the adsorbent in Example 1 of the present invention over time.
[0033] Figure 5 This is a diagram showing the adsorption effect of the adsorbent in Example 1 of the present invention on uranium with different initial concentrations.
[0034] Figure 6 This is a diagram of the recycling of uranium by the adsorbent in Example 1 of the present invention.
[0035] Figure 7 This is a scanning electron microscope (SEM) image of the microscopic morphology of the adsorbent in Example 2 of the present invention.
[0036] Figure 8 This is a graph showing the variation of the adsorption amount of uranium by the adsorbent in Example 2 of the present invention over time.
[0037] Fig. 9 This is a diagram showing the adsorption effect of the adsorbent in Example 2 of the present invention on uranium with different initial concentrations.
[0038] Fig.10 This is a diagram of the recycling of uranium by the adsorbent in Example 2 of the present invention.
[0039] Fig.11 This is a scanning electron microscope (SEM) image of the microscopic morphology of the adsorbent in Example 3 of the present invention.
[0040] Fig.12 This is a graph showing the variation of the adsorption amount of uranium with different initial concentrations by the adsorbent in Example 3 of the present invention over time.
[0041] Fig.13 This is a diagram showing the adsorption effect of the adsorbent on uranium at different temperatures in Example 3 of the present invention.
[0042] Fig.14This is a diagram of the recycling of uranium by the adsorbent in Example 3 of the present invention. DETAILED DESCRIPTION
[0043] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0044] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0045] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0046] Unless otherwise specified, % in this application refers to mass percentage, i.e. wt%.
[0047] The raw materials described in this application are all commercially available products.
[0048] Embodiment 1:
[0049] A method for preparing an indole-modified biomass uranium adsorption material comprises the following steps:
[0050] 1) Weigh 0.5 g of chitosan, 3.15 g of 3-indoleacetic acid, and 0.56 g of p-toluenesulfonic acid monohydrate into a 100 mL two-necked flask, and add 50 mL of formamide solution (50 wt%).
[0051] After stirring and introducing nitrogen for 20 minutes to remove oxygen, stirring and heating were continued at 60°C for 24 hours to allow the grafting reaction to proceed.
[0052] 2) After the reactants in step 1) are cooled (to room temperature), 1.2 mL of glutaraldehyde (mass fraction of glutaraldehyde is 25%) is slowly added, the mixture is sealed again and heated at 60° C. for 12 h to obtain a wet gel.
[0053] 3) filtering the wet gel of the substance in step 2) and sequentially exchanging solvents with acetone and deionized water to remove residual reactants until the filtrate is neutral, indicating that p-toluenesulfonic acid monohydrate and reactants are completely removed.
[0054] 4) Drying by freeze drying. The freeze drying conditions are as follows: freezing the wet gel at -10°C for 36 hours (freezing the gel completely), followed by freeze drying at -50°C and vacuum below 10 Pa for 3 days. After the sample temperature reaches room temperature, take it out and dry it in an oven at 45°C for 1.5 hours to finally obtain the indole-modified biomass uranium adsorption material (adsorbent) S1.
[0055] Adsorption performance test:
[0056] Adsorbent S1 was added to 10 mL of U(VI) solution and stirred at 298 K for 0-360 min. The initial concentration of uranyl ions (solution concentration was 10-250 mg L -1 ) and the effect of solution pH (ranging from 2.0 to 7.5) on the adsorption performance. Figure 2-Figure 6 ,Depend on Figures 2 to 6 It can be seen that when the adsorption equilibrium time is 360min, the maximum adsorption capacity of the adsorbent can reach 837mg / g; after 4 adsorption-desorption cycles, the removal rate of S1 for 10mg / LU (VI) solution can still reach 80%, and it has good adsorption performance for uranium.
[0057] Embodiment 2:
[0058] A method for preparing an indole-modified biomass uranium adsorption material comprises the following steps:
[0059] 1) Weigh 2 g of lignin, 4 g of 3-indoleacetic acid, and 0.44 g of p-toluenesulfonic acid monohydrate into a 100 mL two-necked flask, and add 50 mL of formamide solution (50 wt%).
[0060] After stirring and introducing nitrogen for 20 minutes to remove oxygen, stirring and heating were continued at 70°C for 24 hours to allow the grafting reaction to proceed.
[0061] 2) After the reactants in step 1) are cooled (to room temperature), 4 mL of glutaraldehyde (mass fraction of glutaraldehyde is 25%) is slowly added, the mixture is sealed again and heated at 70° C. for 20 h to obtain a wet gel.
[0062] 3) The wet gel of the substance in step 2) is filtered, and solvent exchange is performed with acetone and deionized water in sequence to remove the residual reactants, until the filtrate is neutral, indicating that p-toluenesulfonic acid monohydrate and the reactants are completely removed.
[0063] 4) Drying by freeze drying. The freeze drying conditions are as follows: freezing the wet gel at -10°C for 40 hours (freezing the gel completely), followed by freeze drying at -50°C and vacuum below 10 Pa for 4 days. After the sample temperature reaches room temperature, take it out and dry it in an oven at 45°C for 2 hours to finally obtain the indole-modified biomass uranium adsorption material (adsorbent) S2.
[0064] Adsorption performance test: adsorbent S1 was added to 10 mL of U(VI) solution and stirred at 298 K for 0-360 min. The initial concentration of uranyl ions (solution concentration was 10-250 mg L -1) and the effect of solution pH (ranging from 2.0 to 7.5) on the adsorption performance. The specific results are shown in Figure 7-Figure 10 ,Depend on Figures 7 to 10 It can be seen that when the adsorption equilibrium time is 120min, the maximum adsorption capacity of the adsorbent can reach 630mg / g; after 5 adsorption-desorption cycles, the removal rate of S2 for 10mg / LU(VI) solution can still reach 80%, and it has good adsorption performance for uranium.
[0065] Embodiment 3:
[0066] A method for preparing an indole-modified biomass uranium adsorption material comprises the following steps:
[0067] 1) Weigh 0.5 g of chitosan, 0.62 g of 3-indoleacetic acid, and 0.56 g of p-toluenesulfonic acid monohydrate into a 250 mL two-necked flask, and add 50 mL of formamide solution (50 wt%).
[0068] After stirring and introducing nitrogen for 20 minutes to remove oxygen, stirring and heating were continued at 60°C for 24 hours to allow the grafting reaction to proceed.
[0069] 2) After the reaction in step 1) is completed, weigh 0.75 g of guar gum, dissolve it in 30 mL of ultrapure water, add it to step 1, and react at 60° C. for 12 h.
[0070] 3) After the reactants in step 2 are cooled (to room temperature), 4 mL of glutaraldehyde (mass fraction of glutaraldehyde is 25%) is slowly added, the mixture is sealed again and heated at 60° C. for 12 h to obtain a wet gel.
[0071] 4) The wet gel of the substance in step 3) is filtered, and solvent exchange is performed with acetone and deionized water in sequence to remove the residual reactants, until the filtrate is neutral, indicating that p-toluenesulfonic acid monohydrate and the reactants are completely removed.
[0072] 4) Drying by freeze drying. The freeze drying conditions are as follows: freezing the wet gel at -10°C for 42 hours, and then freeze drying it at -50°C and a vacuum of less than 10 Pa for 3.5 days. After the sample temperature rises to room temperature, it is taken out and dried in an oven at 45°C for 2 hours to finally obtain the indole-modified biomass uranium adsorption material S3 (adsorbent).
[0073] Adsorption performance test: adsorbent S3 was added to 10 mL of U(VI) solution and stirred at 298 K for 0-360 min. The initial concentration of uranyl ions (solution concentration was 10-250 mg L -1 ) and the effect of solution pH (ranging from 2.0 to 7.5) on the adsorption performance. The specific results are shown in Figure 11-Figure 14 .Depend on Figures 11 to 14It can be seen that when the adsorption equilibrium time is 120min, the maximum adsorption capacity of the adsorbent can reach 360mg / g; after three adsorption-desorption cycles, the removal rate of S3 for 10mg / LU(VI) solution can still reach 82%, and it has good adsorption performance for uranium.
[0074] Comparative Example 1:
[0075] A method for preparing an indole-modified biomass uranium adsorption material comprises the following steps:
[0076] 1) 1 g of guar gum, 2 g of 3-indoleacetic acid, and 0.56 g of p-toluenesulfonic acid monohydrate were weighed and placed in a 100 mL two-necked flask, and 50 mL of formamide solution (50 wt%) was added.
[0077] After stirring and introducing nitrogen for 20 minutes to remove oxygen, stirring and heating were continued at 60°C for 24 hours to allow the grafting reaction to proceed.
[0078] 2) After the reactants in step 1) were cooled (to room temperature), 2 mL of glutaraldehyde (mass fraction of glutaraldehyde was 25%) was slowly added. The mixture was sealed again and heated at 65° C. for 48 h. No wet gel was obtained.
[0079] 3) The reaction solution in step 2) was heated for 7 days and still did not gel, indicating that the target product could not be obtained when the biomass material contained only guar gum.
[0080] Comparative Example 2:
[0081] A method for preparing an indole-modified biomass uranium adsorption material comprises the following steps:
[0082] 1) Weigh 1 g of xanthan gum, 2 g of 3-indoleacetic acid, and 0.56 g of p-toluenesulfonic acid monohydrate into a 100 mL two-necked flask, and add 50 mL of formamide solution (50 wt%).
[0083] After stirring and introducing nitrogen for 20 minutes to remove oxygen, stirring and heating were continued at 60°C for 24 hours to allow the grafting reaction to proceed.
[0084] 2) After the reactants in step 1) were cooled (to room temperature), 1.5 mL of glutaraldehyde was slowly added, but the glutaraldehyde should be evenly mixed in a certain amount of formamide solution. The mixture was sealed again and heated at 65° C. for 48 h, but no wet gel was obtained.
[0085] 3) The reaction solution in step 2) was heated for 7 days and still did not gel, indicating that the target product could not be obtained when xanthan gum was the only biomass material.
[0086] The present invention can also realize the recovery of uranium: the adsorbent is eluted with 0.1 mol / L HCl after the adsorption, and the eluate is collected and concentrated for recovery.
[0087] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
[0088] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A method for preparing an indole-modified biomass uranium adsorbent material, characterized in that The following steps are involved: 1) Mixing a biomass material and a solvent, adding the mixture to indole or its derivatives, adding a catalyst, stirring, and then heating to a certain temperature to react; the biomass material is selected from chitosan or lignin, or a mixture of chitosan, lignin, and any one of xanthan gum and guar gum; the solvent is formamide; the indole or its derivatives are selected from 3-indoleacetic acid, 5-hydroxytryptophan, 4-hydroxyindole, and 5-hydroxyindole; the catalyst is p-toluenesulfonic acid monohydrate; 2) adding a crosslinking agent to the substance obtained in step 1) and continuing the reaction for a period of time to obtain a wet gel; 3) exchanging solvents on the wet gel obtained in step 2) to remove residual reactants; 4) The material obtained in step 3) is freeze-dried to obtain an indole-modified biomass material adsorbent.
2. The method for preparing an indole-modified biomass uranium adsorbent material according to claim 1, characterized in that: In step 1), the molar ratio of the biomass material to indole or its derivative is 1:1-1:6; the concentration range of the added amount of the solvent and the material composition is 1-200 mg / L; and the added amount of the catalyst is 10wt%-80wt% of the biomass material.
3. The method for preparing an indole-modified biomass uranium adsorbent material according to claim 1, characterized in that: In step 1), the mixture is stirred and heated to 60±10° C. The reaction time is 24 hours.
4. The method for preparing an indole-modified biomass uranium adsorbent material according to claim 1, characterized in that: The cross-linking agent in step 2) is glutaraldehyde, and the amount of the cross-linking agent added is 10wt%-30wt% of the biomass material; the reaction time in step 2) is 12-24 hours.
5. The method for preparing an indole-modified biomass uranium adsorbent material according to claim 1, characterized in that: In step 3), the wet gel is subjected to solvent exchange to remove the residual reactant solvent. The specific steps are: during the exchange, acetone and deionized water are used to exchange the solvent in sequence until the filtrate is neutral, indicating that p-toluenesulfonic acid monohydrate and the reactant are completely removed.
6. The method for preparing an indole-modified biomass uranium adsorbent material according to claim 1, characterized in that: The freeze-drying conditions in step 4) are as follows: freeze the wet gel at -10°C for 24-48 hours, then freeze-dry at -50°C and vacuum below 10Pa for 3-5 days. After the sample temperature reaches room temperature, take it out and dry it in a 45°C oven for 1-2 hours.
7. An indole-modified biomass uranium adsorption material prepared by the method according to any one of claims 1 to 6.
8. The use of the indole-modified biomass uranium adsorbent material according to claim 7, characterized in that: The indole-modified biomass uranium adsorption material is used for treating uranium-containing wastewater; the maximum adsorption capacity is 900 mg / g.
